The cladorhizid fauna (Porifera, Poecilosclerida) of the Caribbean and adjacent waters - Hestetun, Jon T.; Pomponi, Shirley A.; Rapp, Hans Tore (Zootaxa, 2016)
The carnivorous sponge family Cladorhizidae has been subject to several recent studies, yet the cladorhizid fauna of the Caribbean and adjacent areas remain comparatively poorly known. In this article we provide a description of the novel species Abyssocladia polycephalus sp. nov. from the Muir Seamount NE of Bermuda, belonging to the mainly Pacific genus Abyssocladia, and Asbestopluma (Asbestopluma) caribica sp. nov. from the Beata Ridge. Additionally, we provide a re-description of the poorly known species Chondrocladia (Chondrocladia) verticillata Topsent, 1920, and compare this species with the closely related species C. (C.) concrescens Schmidt, 1880. Finally, we provide a brief overview of the carnivorous sponges known from the Gulf of Mexico, Caribbean Sea and adjacent Atlantic Ocean.